Selection Signatures of Pacific White Shrimp Litopenaeus vannamei Revealed by Whole-Genome Resequencing Analysis - Wang, Hao; Teng, Mingxuan; Liu, Pingping; Zhao, Mingyang; Wang, Shi; Hu, Jingjie; Bao, Zhenmin; Zeng, Qifan (Frontiers in Marine Science, 2022)
The Pacific white shrimp Litopenaeus vannamei is among the top aquatic species of commercial importance around the world. Over the last four decades, breeding works of L. vannamei have been carried out intensively and have generated multiple strains with improved production and performance traits. However, signatures of domestication and artificial selection across the L. vannamei genome remain largely unexplored. In the present study, we conducted whole genomic resequencing of 180 Pacific white shrimps from two artificially selective breeds and four market-leading companies. A total of 37 million SNPs were identified with an average density of 22.5 SNPs/Kb across the genome. Ancestry estimation, principal component analysis, and phylogenetic inference all revealed obvious stratifications among the six breeds. We evaluated the linkage disequilibrium (LD) decay in each breed and identified genetic variations driven by selection. Pairwise comparison of fixation index (Fst) and nucleotide diversity (θπ) allowed for mining genomic regions under selective sweep in each breed. Functional enrichment analysis revealed that genes within these regions are mainly involved in cellular macromolecule metabolic process, proteolysis, structural molecule activity, structure of constituent ribosome, and responses to stimulus. The genome-wide SNP datasets provide valuable information for germplasm resources assessment and genome-assisted breeding of Pacific white shrimp, and also shed light on the genetic effects and genomic signatures of selective breeding.